Bhartrhari - John Britto Chethimattam (Journal of Dharma, 1978)
In the Indian tradition language, logic, psychology, metaphysics and even mystical experience were treated in intimate relationship almost like concentric circles around the conscious self that radiates its inner light through the different layers or sheathes of personality. Harold G. Coward who had a deep interest in "epistemological psychology" and knowledge through language and felt frustrated by the academic alienation between philosophy, psychology and theology in the West, finds in Bhartrhari, the ahcient linguistic philosopher-mystic of India a kindred spirit. The book which is study of Bhartrhari’s principal work Vakyapadi-ya ex plores the impact of language and meaning in Yoga psychology, aesthetics and religion, But the paradox of Bhartrhari’s holistic interest is that it is expressed in Sanskrit, a language removed from the emotional, responses of everyday life.